Rapid detection and enumeration of pathogenic Vibrio parahaemolyticus in raw vegetables from retail outlets - Robin, Tunung; Mohamad Ghazali, Farinazleen; Mohd Adzahan, Noranizan; Kantilal, Haresh Kumar; Bilung, Lesley Maurice; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study aims to determine the frequency and density of potentially pathogenic Vibrio parahaemolyticus, defned as those possessing thermostable-direct hemolysin (tdh) and/or tdh-related hemolysin (trh) genes, in raw salad vegetables at retail level in Selangor, Malaysia. A combination of Most Probable Number - Polymerase Chain Reaction (MPN-PCR) method was applied to detect the presence of tdh and/or trh gene-possessing V. parahaemolyticus and to enumerate their density in the samples. A total of 276 samples of vegetables commonly eaten raw in Malaysia (Cabbage = 30; Carrot = 31; Cucumber = 28; Four winged bean = 26; Indian pennywort = 17; Japanese parsley = 21; Lettuce = 16; Long bean = 32; Sweet potato = 29; Tomato = 38; Wild cosmos = 8) were analyzed. The samples were purchased from two supermarkets (A and B) and two wet markets (C and D). With the MPN-PCR technique, about 12.0% of the samples were positive for the presence of V. parahaemolyticus tdh-positive, with maximum densities of up to 39 MPN/g. The total frequency of V. parahaemolyticus trh-positive in the samples was 10.1%, with maximum concentration 15 MPN/g. V. parahaemolyticus tdh-positive was most prevalent in samples from Wet Market C (20.78%) and also in vegetable type Oenanthe stolonifera (Japanese parsley) with 19.0%, while V. parahaemolyticus trh-positive was predominant in samples from Wet Market D (16.7%) and was most frequent in both Oenanthe stolonifera (Japanese parsley) and Cucumis sativus (Cucumber) with 14.3% prevalence for each type. The results highlighted the fact that raw vegetables could be contaminated with virulent V. parahaemolyticus and could act as a transmission route, thus poses risk to consumers from the consumption of raw vegetables. To the author’s knowledge, this is the first assessment of V. parahaemolyticus carrying tdh and trh genes in raw vegetables from retail outlets in Malaysia.